Evaluation of the Efficacy of Different Cleaning Methods for Orthodontic Thermoplastic Retainers in terms of Bacterial Colonization - Filiz Aydoğan Akgün; Neslihan Ebru Şenışık; Emel Sesli Çetin (Galenos Yayinevi, 2019)
Objective:This study investigated the antimicrobial efficacy of three different cleaning methods on Streptococcus mutans (SM) and Lactobacillus (LB) bacteria colonization in vivo. The three different cleaning methods were applied by volunteers on clear vacuum formed retainers (VFRs).Methods:In this prospective, cross-over study, a total of 21 volunteers were included. All VFRs used by the volunteers were cleaned using three different cleaning methods in a sequence. These methods were peroxide-based cleanser tablets (PBCTs) plus brushing, control (only brushing), and vinegar plus brushing, respectively. The obtained salivary, VFR material, and periodontal data were statistically compared by factorial design repeated measures analysis of variance.Results:The SM and LB bacteria counts on VFRs after using both PBCTs and vinegar were statistically similar (p>0.05), but bacteria counts were statistically lower than the control method (p<0.01). There were no statistically significant differences between the SM and LB bacteria counts in saliva samples taken before and after the application of the cleaning methods (p>0.05). Similarly, there were no significant differences between periodontal data obtained from plaque and bleeding indices at all study times. The periodontal pocket depth gradually decreased in the successively performed cleaning applications (p<0.05).Conclusion:The application of PBCTs and vinegar to VFRs at sequential time intervals resulted in similar bacteria counts. The higher LB counts and similarly higher SM counts on the VFR samples indicate that mechanical cleaning only (control method) is not adequate to obtain hygiene. Salivary flora was not correlated with bacteria counts of VFRs.